2012
DOI: 10.1021/ja307861n
|View full text |Cite
|
Sign up to set email alerts
|

Stereospecific Cross-Coupling of Secondary Organotrifluoroborates: Potassium 1-(Benzyloxy)alkyltrifluoroborates

Abstract: Potassium 1-(alkoxy/acyloxy)alkyltrifluoroborates have been synthesized through a copper-catalyzed diboration of aldehydes and subsequent conversion of the resulting potassium 1-(hydroxy)alkyltrifluoroborates. The palladium-catalyzed Suzuki-Miyaura reaction employing the potassium 1-(benzyloxy)alkyltrifluoroborates with aryl and heteroaryl chlorides provides access to protected secondary alcohols in high yields. The β-hydride elimination pathway is avoided through use of the benzyl protecting group, which is p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
113
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 186 publications
(119 citation statements)
references
References 74 publications
4
113
0
2
Order By: Relevance
“…43 These materials could be prepared in high enantiomeric purity, and in contrast to 2°alkyl systems (eq 30), the cross-coupling transpired with retention of configuration with extremely high stereochemical fidelity. A rationale for both the stereochemistry of the transmetalation and the lack of β-hydride elimination/ isomerization that often accompanies 2°alkyl cross-coupling was proposed.…”
Section: Scheme 1 Detailed Mechanism Of Aryltrifluoroborate Crosscoumentioning
confidence: 99%
“…43 These materials could be prepared in high enantiomeric purity, and in contrast to 2°alkyl systems (eq 30), the cross-coupling transpired with retention of configuration with extremely high stereochemical fidelity. A rationale for both the stereochemistry of the transmetalation and the lack of β-hydride elimination/ isomerization that often accompanies 2°alkyl cross-coupling was proposed.…”
Section: Scheme 1 Detailed Mechanism Of Aryltrifluoroborate Crosscoumentioning
confidence: 99%
“…When using chiral secondary alkylboron intermediates, these issues are compounded by the challenge of stereocontrol (control of the configuration of a stereogenic carbon). Indeed, although some progress has been realized in recent years [7][8][9][10][11][12][13][14][15][16][17][18][19][20] , control of stereoselectivity is viewed as one of the final frontiers in the Suzuki Miyaura reaction (Fig. 1b) 21 .…”
mentioning
confidence: 99%
“…The benzyloxy group is thought to prevent competing β-hydride elimination by acting as a hemilabile ligand [77]. Prior research has demonstrated that these types of ligands can serve several roles in the prevention of β-hydride elimination.…”
Section: Stereoselective Couplings Of Alkyl Boronates With Aryl or Almentioning
confidence: 99%